Dampak Perubahan Cuaca Pada Pendapatan Masyarakat Nelayan di Pantai Nelayan - Hajrina Hajrina; Tahir Tahir; La Ode Amaluddin; Andrias Andrias (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Weather changes are the most vulnerable thing to happen in Nelayan Beach. So, if there is a change in the weather, it will cause fishermen's income to be unstable. The aim of this research is to determine the income of fishermen regarding the impact of weather changes on fishing communities and to determine the effect of weather changes on the income of fishing communities. This type of research is descriptive qualitative. The results of this research show that the income of fishermen in Watolo Village, Mawasangka District is very influenced by the weather, where when the weather is good, the fishing community will go to sea for approximately 10-22 hours, but if the weather conditions are bad, the fishermen will go to sea for 2-4 hours a day. The fisherman's catch is not all will be bought and sold but used to fulfill daily meals. It is difficult to predict weather conditions by looking at cloud and wind conditions which prevent fishermen from going to sea.